Analisis Struktur Teks Eksplanasi pada Media Online Tirto.id sebagai Bahan Ajar Modul Teks Eksplanasi di Kelas VIII - Marziamin, Anggela; Ibnu Adham, M. Januar; Setiawan, Hendra (Jurnal Pendidikan : Riset dan Konseptual, 2025)
This study is entitled Analysis of Explanatory Text Structure in the Online Media Tirto.id as Teaching Material for Explanatory Text Modules in Class VIII. The menthod used in this study is a qualitative descriptice menthod. Qualitative descriptive involves the collection of data by describing or depicting the data through descriptive words that illustrate the research subject. The aims of this research 1) describe the analysis of the explanatory text structure in the online media tirto.id, 2) describe the utilization of the analysis results of the explanatory text structure in the online media tirto.id as teaching material for class VIII.